The development of deformable bodies collision response algorithm for interactive virtual environment - Mohd. Shuaib, Norhaida; Bade, Abdullah; Daman, Daut; Sunar, Mohd. Shahrizal (Faculty of Computer Science and Information System, 2006)
Physical based deformation method usually suffers from high computation cost which does not favors practical interactive applications, even if the deformation only occurs in a small area of the deformable object. This thesis proposed a dynamic selection based method for small area deformation to maintain interactivity with high geometric complexity of volumetric mesh by reducing areas for deformation processing. It is an optimization algorithm that selects small areas for deformation processing based on equilibrium state. Assuming no external forces other than concentrated loads, the optimization algorithm succeeded to reduce deformation computation for physical based deformation systems. The method is suitable for real time application like virtual surgery.